The Influence of Organizational Culture and Organizational Commitment on Organizational Citizenship Behavior through job Satisfaction In Dental and Oral Hospital Nala Husada Surabaya - Tandy Izzud Alauddin; Eddy Yunus (Economic and Bussiness Faculty, Dr Soetomo University, 2022)
Abstract. The purpose of this study was to analyze the effect of organizational culture and organizational commitment on job satisfaction, analyze the influence of organizational culture and organizational commitment on Organizational Citizenship Behavior, and analyze the effect of job satisfaction on Organizational Citizenship Behavior at Nala Husada Dental and Oral Hospital Surabaya. This type of research is explanatory research with a quantitative method approach. The data collection method used a questionnaire distributed to 36 employees of the Nala Husada Dental and Oral Hospital in Surabaya. The data analysis technique used is Structural Equation Modeling analysis using Partial Least Square. The results of the study show that organizational culture has a significant effect on job satisfaction. Organizational Commitment has no significant effect on Job Satisfaction. Organizational culture and organizational commitment have a significant effect on organizational citizenship behavior. Job Satisfaction has a significant effect on Organizational Citizenship Behavior at Nala Husada Dental and Oral Hospital Surabaya.Keywords: Organizational Culture; Organizational Commitment, Job Satisfaction; and Organizational Citizenship Behavior